(untitled) (Bangladesh Journal of Bioethics, 2019)
Dear Sir/Madam You are cordially invited to attend the inaugural session of 20th Asian Bioethics conference organized by Bangladesh Bioethics Society in cooperation with SSRC, Planing Division; PMR, DGHS, Ministry of Health & Family Welfare, BMRC, ABA and Eubios Ethics Institute on Friday, 22 Nov, 2019 at NEC Auditorium, Planning Ministry, Agargoan, Dhaka. We would appreciate your presence in the programme.